T-Polyform Modules - Ali, Inaam Mohammed; Elewi, Alaa A. (Iraqi Journal of Science, 2019)
We introduce the notion of t-polyform modules. The class of t- polyform modules contains the class of polyform modules and contains the class of t-essential quasi-Dedekind. Many characterizations of t-polyform modules are given. Also many connections between these class of modules and other types of modules are introduced.